An Attempt to Improve Teachers' Commitment to Carrying Out Their Duties Through Coaching Activities at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan - Yayuk Indarwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper examines whether the teacher's commitment to carrying out assignments can be increased through coaching at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan. Based on the description of the background, identification, and limitation of the problems, the research is focused on an attempt to increase teacher commitment in carrying out their duties through coaching activities at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan. This school action research was carried out at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan. Under the supervision of the principal himself, it was selected because it totally supports the principal's task to determine and try to increase teacher commitment in carrying out their duties through coaching activities. The research was conducted in two cycles. The duration of the research was approximately two months and up to now the training is still being held occasionally, but in other schools. Hence, this research started in September 2022 and ended in October 2022. based on the description of data processing and discussion, it is concluded that the teacher's commitment to carrying out their duties was obtained in cycle I at 64% in the good category and increased to 84% in the good category in cycle II. It means that coaching activities to increase teacher commitment in carrying out their duties at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan are considered successful.